The effect of autoregulatory progressive resistance exercise vs. linear periodization on strength improvement in college athletes - Mann, J. B.; Thyfault, J. P.; Ivey, P. A.; Sayers, S. P. (The Journal of Strength and Conditioning Research, 2010)
Autoregulatory progressive resistance exercise (APRE) is a method by which athletes increase strength by progressing at their own pace based on daily and weekly variations in performance, unlike traditional linear periodization (LP), where there is a set increase in intensity from week to week. This study examined whether 6 weeks of APRE was more effective at improving strength compared with traditional LP in division I College football players. We compared 23 division 1 collegiate football players (2.65 ± 0.8 training years) who were trained using either APRE (n = 12) or LP (n = 11) during 6 weeks of preseason training in 2 separate years. After 6 weeks of training, improvements in total bench press 1 repetition maximum (1RM), squat 1RM, and repeated 225-lb bench press repetitions were compared between the APRE and LP protocol groups. Analysis of variance (ANOVA) and analysis of covariance (ANCOVA) were used to determine differences between groups. Statistical significance was accepted at p = 0.05. Autoregulatory progressive resistance exercise demonstrated greater improvement in 1RM bench press strength (APRE: 93.4 ± 103 N vs. LP: -0.40 ± 49.6 N; ANCOVA: F = 7.1, p = 0.02), estimated 1RM squat strength (APRE: 192.7 ± 199 N vs. LP: 37.2 ± 155 N; ANOVA: F = 4.1, p = 0.05) and the number of repetitions performed at a weight of 225 lb (APRE: 3.17 ± 2.86 vs. LP: -0.09 ± 2.40 repetitions; ANCOVA: F = 6.8, p = 0.02) compared with the LP group over the 6-week training period. Our findings indicate that the APRE was more effective than the LP means of programming in increasing the bench press and squat over a period of 6 weeks.